Analisis Sentimen Terhadap Bullying Di Indonesia Pada Twitter Menggunakan Naïve Bayes dan SVM - AlHakim, Abdu Malik; Leonardo D.P, Harun; Putri, Alifia Nursyahrani (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
Bullying has become a serious social problem in Indonesia. In the past few years, bullying cases are increasing, especially among children and adolescents. Bullying can occur anywhere, including at home, work, community, social media, and school, but it is most common in educational settings. Twitter or